Tranexamic Acid: Promise or Panacea. (January 2018) - Cornelius, Brian G.; McCarty, Karen; Hylan, Kristi; Cornelius, Angela; Carter, Keith; Smith, Kenneth W. G.; Ristic, Srdan; Vining, Daniel; Cvek, Urska; Trutschl, Marjan
Abstract : The MATTERs and CRASH-2 studies demonstrate that tranexamic acid (TXA) reduces mortality in patients with traumatic hemorrhage. However, their results, conducted in foreign countries and with U.S. military soldiers, provoke concerns over generalizability to civilian trauma patients in the United States was reported. The evaluation of patient outcomes following treatment with TXA by a civilian air medical program. A retrospective chart review of trauma patients transported by air service to a Level 1 trauma center was conducted. For the purposes of intervention evaluation, patients meeting this criterion for the 2 years (2012–2014) prior to therapy implementation were compared with patients treated during the 2-year study period (2014–2016). Goals were to evaluate morbidity, mortality, and length of stay. During the review, 82 control and 49 study patients were identified as meeting inclusion criteria. Patients in the control group were found to be less acute, which correlated with shorter hospital stays and better discharge outcomes. Multiple patients in the study group who should have expired according to a significantly elevated Trauma Revised Injury Severity Score (TRISS) survived, whereas multiple patients in the control group expired despite a low TRISS calculation. This is the first outcome-based study conducted in a U.S. trauma system. The outcomes in civilian trauma patients in the United States do not follow that of the previous MATTERs and CRASH-2 studies. However, this study still shows benefit to TXA administration and reduced risk for administration to patients with head trauma and occurrence of venous thromboembolism. Randomized control trials are needed to evaluate the role of TXA administration in the United States.